Efficiency Of Generator Set On Changes In Electrical Load On Fishery Vessels - Rama Arya Sobhita; Akhmad Azhar Firdaus; Fahmi Yahya Saputra; Anggara Trisna Nugraha (P3M Politeknik Perkapalan Negeri Surabaya, 2024)
Electrical energy is an essential requirement for fishing vessels, and it is primarily generated by diesel-driven electric generators. This energy is utilized for various purposes onboard such as lighting, navigation, and supporting fishing activities including loading and unloading. The efficient operation and longevity of the electric generator onboard depend on ensuring that the load imposed on it does not surpass its capacity. Researchers conducted several phases in this study, including identifying the electrical power distribution system, determining the generator capacity and the electrical load it receives, and calculating the electrical load under various operational conditions. Additionally, the study examined the operational efficiency of the generator under four different conditions. The findings reveal that the fishing vessel employs a radial electrical distribution system and is equipped with two electric generators, each having a capacity of 225 kVA. The generators demonstrate efficient performance across all operational scenarios, with load factors ranging from 79.70% to 83.08%.